Incorporating conceptual site models into national-scale environmental risk assessments for legacy waste in the coastal zone - Riley, Alex L.; Amezaga, Jaime; Burke, Ian T.; Byrne, Patrick; Cooper, Nick; Crane, Richard A.; Comber, Sean D.W.; Gandy, Catherine J.; Hudson-Edwards, Karen A.; Jennings, Elin; Lewis, Elizabeth; Lofts, Stephen; et al. (Frontiers in Environmental Science, 2022)
Solid wastes deposited in the coastal zone that date from an era of lax environmental regulations continue to pose significant challenges for regulators and coastal managers worldwide. The increasing risk of contaminant release from these legacy disposal sites, due to a range of factors including rising sea levels, associated saline intrusion, and greater hydrological extremes, have been highlighted by many researchers. Given this widespread challenge, and the often-limited remedial funds available, there is a pressing need for the development of new advanced site prioritization protocols to limit potential pollution risks to sensitive ecological or human receptors. This paper presents a multi-criteria decision analysis that integrates the principles of Conceptual Site Models (Source-Pathway-Receptor) at a national scale in England and Wales to identify legacy waste sites where occurrence of pollutant linkages are most likely. A suite of spatial data has been integrated in order to score potential risks associated with waste type (Source), likelihood of pollutant release relating to current and future flood and erosion climate projections, alongside current management infrastructure (Pathway), and proximity to sensitive ecological features or proxies of human use in coastal areas (Receptors). Of the 30,281 legacy waste deposits identified in England and Wales, 3,219 were located within the coastal zone, with coastal areas containing a density of legacy wastes (by area) 10.5 times higher than inland areas. Of these, 669 were identified as priority sites in locations without existing coastal defences or flood management infrastructure, with 2550 sites identified in protected areas where contaminant transfer risks could still be apparent. The majority (63 %) of the priority sites have either undefined source terms, or are classified as mixed wastes. Mining and industrial wastes were also notable waste categories, and displayed strong regional distributions in the former mining areas of north-east and south-west of England, south Wales, and post-industrial estuaries. The large-scale screening process presented here could be used by environmental managers as a foundation to direct more high-resolution site assessment and remedial work at priority sites, and can be used as a tool by governments for directing funding to problematic sites.